2014
DOI: 10.1007/s12262-013-1029-7
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Müllerian Duct Syndrome (PMDS): a Rare Anomaly the General Surgeon Must Know About

Abstract: Persistent Müllerian duct syndrome is a rare condition occasionally encountered in men with normal phenotype but with presence of Müllerian duct structures. In India, owing to neglect and lack of facilities, we encounter this condition in adult males. We encountered on the same day in the operation theatre two phenotypic males aged 40 years and 10 months who had inguinal hernia on one side along with contralateral undescended testis. Both patients intraoperatively had uterus with fallopian tubes and underwent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 19 publications
0
16
0
2
Order By: Relevance
“…In the literature, sterility is indeed the rule, but normal spermatogenesis has also been reported. A thorough literature search found that 19% of reported adult patients fathered 1 or more children [Karimi-Nejad et al, 1988;Farag, 1993;Berkmen, 1997;Aboutorabi et al, 2005;Liang et al, 2006;Jaka and Shankar, 2007;Prakash et al, 2009;Sichani et al, 2009;Inuganti et al, 2011;Kaore and Kaore, 2012;Kumar and Mohan, 2012;Kovachev et al, 2014;Sherwani et al, 2014;Agrawal and Kataria, 2015;Modi et al, 2015]. Farag [1993] reported a proportion of 11% of fertile patients in Kuwait and neighboring populations.…”
Section: Infertilitymentioning
confidence: 99%
“…In the literature, sterility is indeed the rule, but normal spermatogenesis has also been reported. A thorough literature search found that 19% of reported adult patients fathered 1 or more children [Karimi-Nejad et al, 1988;Farag, 1993;Berkmen, 1997;Aboutorabi et al, 2005;Liang et al, 2006;Jaka and Shankar, 2007;Prakash et al, 2009;Sichani et al, 2009;Inuganti et al, 2011;Kaore and Kaore, 2012;Kumar and Mohan, 2012;Kovachev et al, 2014;Sherwani et al, 2014;Agrawal and Kataria, 2015;Modi et al, 2015]. Farag [1993] reported a proportion of 11% of fertile patients in Kuwait and neighboring populations.…”
Section: Infertilitymentioning
confidence: 99%
“…In the literature, sterility is indeed the rule but normal spermatogenesis has been reported. A thorough literature search found that 19% of reported adult patients fathered one or more children [Karimi-Nejad et al 1988;Farag, 1993;Berkmen, 1997;Aboutorabi et al, 2005;Liang et al, 2006;Jaka and Shankar, 2007;Prakash et al, 2009;Sichani et al, 2009;Inuganti et al, 2011;Kaore and Kaore, 2012;Kumar and Mohan, 2012;Kovachev et al, 2014;Sherwani et al, 2014;Agrawal and Kataria, 2015;Modi et al, 2015]. Farag et al [1993] reported an 11% proportion of fertile patients in Kuwait and neighboring populations.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…Los defectos en el gen FIM conducen a la persistencia de un útero y una trompa de Falopio en los hombres. [10][11][12] Clínicamente, los casos de SPCM se dividen en cuatro categorías (Tabla 1). Nuestro caso estaría en un cuarto grupo de niños con escroto vacío unilateral y testículo normal contralateral, lo cual es lo más infrecuente.…”
Section: Discussionunclassified